A Rare Case of Benign Synchronous Neoplasm of Parotid Salivary Gland - Mithun, Vijayabasker; Karuppusamy, Usha Rani; Balasubramanian, Nandhini Bala; Rajan, Mahudeswaran (Annals of Pathology and Laboratory Medicine, 2024)
Introduction Salivary gland neoplasms represent 2–6% of all head and neck neoplasms. Salivary gland neoplasms arising from the major salivary glands are predominantly benign. Pleomorphic adenoma is the most common benign neoplasm of the salivary gland, followed by warthin’s tumour. The synchronous occurrence of both of these neoplasms is rarely described. We present a case of unilateral salivary gland neoplasm with two distinct histological lesions, which were found incidentally during gross examination and confirmed microscopically. Case report A 72-year-old man with complaints of left parotid swelling, which progressively increased in size over the past 6 months. Ultrasound imaging studies and FNAC show features of pleomorphic adenoma, for which the patient underwent surgery, and the specimen was sent for histopathological examination. In the gross examination, a tan-brown area measuring 0.6 cm in greatest dimension was noted in the parotid salivary gland, in addition to the encapsulated grey-brown neoplasm. Histologically, the tan-brown lesion was found to be an intranodal warthin’s tumour along with a pleomorphic adenoma. Conclusion Synchronous neoplasm is a rare entity that can easily be missed in clinical, imaging and even in cytological examinations. Proper histopathological examination of the resected specimens helps in identifying the lesions that were left unrecognized even by imaging studies due to their proximity to the existing neoplasm, as in our case. The use of VTIQ in combination with B-mode ultrasound may be beneficial in detecting the nature of the lesion prior to surgery.